Ponceau S Dye Removal Using UV/Chlorine Process: Affecting Factors, COD Removal and Comparison with UV/H2O2 and UV/Persulfate Systems - Chatib, Baylassane; Laftani, Yasmine; Boussaoud, Abdelghani; Hachkar, Mohsine (Universitas Gadjah Mada, 2025)
The purpose of this work was to examine the degradation of Ponceau S (PS) using the UV/chlorine process under various operating parameters. The temporal evolution of the conductivity and the chemical oxygen demand (COD) of the reaction medium were also investigated. The degradation efficiency of PS by UV/chlorine process was compared to other advanced oxidation processes, such as UV/S2O82− and UV/H2O2 processes. All reaction kinetics exhibited pseudo-first-order kinetics with respect to PS dye and their apparent rate constants were: kapp(UV/H2O2) = 0.0519 min−1 < kapp(UV/S2O82−) = 0.0746 min−1 < kapp(UV/chlorine) = 0.283 min−1. The action of solar irradiation on the PS degradation was appreciably effective. At pH = 4.22 and when [chlorine] = 0.2 mM, PS degradation using UV/chlorine process yielded more than 70% in only 10 min of dye degradation. The presence of inorganic anions showed an inhibition effect on decolorization kinetics for carbonate species compared to that observed for sulfates. The high COD removal efficiency was obtained for UV/persulfate process (73%) in comparison with that obtained for other AOPs.